2018
DOI: 10.1017/s1352465817000844
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of Pathways to Inflated Responsibility Beliefs in Children with Obsessive Compulsive Disorder

Abstract: Results provide initial support for the theory proposed by Salkovskis et al. (1999) as applied to youth with OCD. Future studies are needed to further assess the model in early-onset OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…An overvalued sense of responsibility has been most consistently associated with OCD. [28] Salkovskis et al . [29] proposed that experiencing heightened responsibility, overprotective parents and rigid rules, and thinking that one influenced or caused a negative life event act as “pathways” to the development of inflated responsibility beliefs, thereby increasing risk for OCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An overvalued sense of responsibility has been most consistently associated with OCD. [28] Salkovskis et al . [29] proposed that experiencing heightened responsibility, overprotective parents and rigid rules, and thinking that one influenced or caused a negative life event act as “pathways” to the development of inflated responsibility beliefs, thereby increasing risk for OCD.…”
Section: Discussionmentioning
confidence: 99%
“…[29] proposed that experiencing heightened responsibility, overprotective parents and rigid rules, and thinking that one influenced or caused a negative life event act as “pathways” to the development of inflated responsibility beliefs, thereby increasing risk for OCD. In fact, overvalued sense of responsibility has been proposed as a target for both prevention and management in OCD;[28] cognitive restructuring techniques to address this phenomenon would also help facilitate insight into illness. These phenomena are understudied in children.…”
Section: Discussionmentioning
confidence: 99%
“…early experiences (Briggs and Price, 2009), critical incidents (Rhéaume et al, 1998), responsibility assumptions and beliefs (Abramowitz et al, 2003;Romero-Sanchiz et al, 2015), misinterpretation of intrusive thoughts (Abramowitz et al, 2006), neutralizing actions (Salkovskis et al, 1997), attention bias (Amir et al, 2009), counterproductive safety strategies (Abramowitz et al, 2001) and mood changes (Purdon, 2001). In addition, there is also support for the proposed relational pathways within the model, with early experiences and critical incidents being linked to the formation and activation of maladaptive beliefs around responsibility Collins and Coles, 2018) and the misinterpretation of intrusions having a crucial mediating role between maladaptive beliefs and symptoms of OCD (Pleva and Wade, 2006). However, these pathways have typically been examined in isolation and have not been concurrently examined in a comprehensive test of the model.…”
Section: Introductionmentioning
confidence: 94%
“…A large amount of observational and experimental studies in clinical and non-clinical adult samples demonstrated the association between obsessive beliefs and OCD [16], but not all the studies supported this relationship [17]. Moreover, some of the so-called obsessive beliefs may not be speci c of OCD, i.e., they are also associated with anxiety or depressive symptoms or disorders, and some beliefs may be more strongly related to OCD than other [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The speci city of In ated Responsibility beliefs to OCD was investigated through a meta-analysis of 58 studies (n = 15678) including studies in children or adolescents [17]. The results showed a medium effect size of this association, although there was a signi cant difference between the effect sizes in adult versus child-adolescent samples: In ated Responsibility beliefs appeared more strongly endorsed by adults than by children/adolescents [16]. In addition, this domain was more strongly associated with OCD than with depressive disorders, but equally with anxiety disorders [16].…”
Section: Introductionmentioning
confidence: 99%